Design and evaluation of a sustainable blended study programme in higher education - Versteijlen, Marieke; Wals, Arjen E. J.; van Wee, Bert (Frontiers in Education, 2023)
Introduction: Blended learning, i.e. a mix of online and in-class education, can be deployed for enhancing the educational quality and resilience in higher education (HE). It may also contribute to HE's sustainability objectives by lowering the carbon emissions of students commuting to campus. In this study, pedagogical design principles for sustainable blended learning and teaching are developed and evaluated taking into account these opportunities.A prototype for a sustainable blended study programme at a University of Applied Sciences was developed and evaluated using a form of Educational Design Research.The design stage, carried out by a team of eight lecturers, resulted in a design based on six pedagogical design principles. This design also included an effort to reduce student travel by limiting on-campus education to two days a week. The results show the effects of students' increased online learning skills and diminished travel movements on their satisfaction with the blended learning design, and their travel behaviour, which can lead towards an attitude change regarding commute and 2 This is a provisional file, not the final typeset article online learning. The lecturers' observations and experiences, depending on their personal preferences, contradicted (self-regulation skills) as well as confirmed (online learning experiences) the students' evaluations.The developed design principles are important to support a new balance between virtual and physical spaces, learning activities, moments in time and sustainability.